Penggunaan Layanan Penguasaan Konten untuk Meningkatkan Daya Juang Mahasiswa Prodi BK Unindra - Miskanik, Miskanik; Yuli Haryanto (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research explores the impact of using content mastery services on increasing the fighting power of students in the Counseling Guidance (BK) Study Program at Indraprasta PGRI University (Unindra). The research method involves literature review, service implementation, and results analysis to evaluate the effectiveness of the service. The results show an increase in students' mastery of academic content and critical thinking abilities. This increase has a positive impact on students' academic achievement and career readiness. The findings of this research support the importance of implementing content mastery services as a strategy to strengthen students' competitiveness at the higher education level.